Sexual Attitude and Potential Sexual Risk Behaviors Among Youth: Basis for a School Based Prevention Program - Lazaro, Rosdy; Regudon, Rommel; Sullestre, Angel; Coronejo, John Lloyd Kenneth; Jupia, Glayza; ALBARRACIN, RODIMEL (12th International Scholars Conference 2025, 2026)
Abstract –This study utilized a quantitative descriptive–correlational design to investigate the relationship between sexual attitude and potential sexual risk behaviors among 188 Bachelor of Education students majoring in Elementary Education at a state university in Quezon Province, Philippines. The data were examined with descriptive statistics, ANOVA, and Pearson's correlation coefficient. The findings indicated that participants had favorable sexual attitudes (M = 2.78, SD = 0.26) and possessed a moderate understanding of sexual risk behaviors (M = 2.70, SD = 0.24), although displayed diminished cultural awareness of these risks (M = 2.41, SD = 0.42). This indicates that cultural ideas, traditions, and taboos may restrict candid discourse and comprehension of sexual issues. ANOVA results indicated no significant differences related to age (F = 2.501, p = 0.085) or sexual orientation (F = 0.555, p = 0.575), however grade level had a significant influence (F = 3.751, p = 0.025), suggesting that awareness and attitudes may evolve with academic advancement. Correlation analysis indicated a low positive correlation between sexual attitudes and knowledge of sexual risk behaviors (r = 0.31, R² = 0.10, p = 0.000) and a moderate negative correlation between sexual attitudes and cultural factors (r = –0.40, R² = 0.16, p = 0.000). These findings corroborate E.B. Tylor and Lewis Henry Morgan’s Cultural Evolution Theory, emphasizing the adaptability and longevity of culture over time. The study offers critical insights into kids' sexual attitudes, knowledge, and cultural influences, serving as a vital foundation for the development of culturally appropriate and effective school-based prevention programs.